Hyperthermia-mediated cell death via deregulation of extracellular signal-regulated kinase and c-Jun NH2-terminal kinase signaling - Enomoto, Atsushi; Fukasawa, Takemichi; Yoshizaki, Ayumi (Frontiers in Cell Death, 2024)
Hyperthermia is a promising anticancer treatment that induces heat stress, thereby stimulating various signal transduction pathways to maintain cellular homeostasis. Mitogen-activated protein kinases (MAPKs) associate various extracellular stimuli with cytoplasmic and nuclear mediators through a three-tiered cascade of kinases, including MAPKs, MAP2Ks, and MAP3Ks. In mammals,three major groups of MAPKs have been characterized: extracellular signal-regulated protein kinases (ERK1/2), p38 MAPKs (α, β, γ, and δ), and c-Jun NH2-terminal kinases (JNK1/2/3). Each group of MAPKs is activated by heat and exhibits distinct biological functions. Recent studies have indicated that in hyperthermia, MAPK signaling pathways regulate cell survival and death in unique ways. This review offers a concise overview of the MAPK signaling pathway, specifically ERK and JNK, focusing on their relevance in cancer, interplay with heat shock proteins or phosphatases, and current understanding of the MAPK signaling pathway in hyperthermia.